Ideological attitudes predicting online hate speech: the differential effects of right-wing authoritarianism and social dominance orientation - Dellagiacoma, Laura; Geschke, Daniel; Rothmund, Tobias (Frontiers in Social Psychology, 2024)
Introduction While research on online hate speech (OHS) has expanded in recent years, only few studies adopt a theoretical framework to understand how ideological attitudes differentially motivate individuals to engage with OHS. Drawing on the dual-process motivational model of ideology and on previous political psychological research on OHS, this study examines how individual levels of social dominance orientation (SDO) and right-wing authoritarianism (RWA) predict the likelihood of producing OHS for online platforms users. Methods We used logistic regressions to analyze the survey data from a representative German sample of social media platform users (N = 7,349). Results The analyses indicate that SDO is related with higher odds of producing OHS, while RWA is related with lower odds. After adjusting for socio-economic factors and controlling for alternative predictors, the odd ratios remain significant, indicating that these two ideological attitudes predict online hate speech in different directions. Discussion The results show that high-RWA individuals are less likely to engage with OHS, which is explained through their conservative motivation to conform to social norms and maintain social stability. High-SDO individuals are more likely to produce OHS and may use it following their competitive motivation to increase hierarchical relations and improve their social status within society. The findings are discussed taking into consideration the specificities of the German social context, and corroborate and expand previous research. From these subtle but crucial differential effects, relevant implications are drawn for the platform as well as for social and political levels.